La vivienda vernácula en Burkina Faso: transformaciones de los modos de habitar de las culturas del Sahel - Sánchez, María Aguilar; Melendo, José Manuel Almodóvar (El Colegio de México, 2020)
Burkina Faso is a country in sub-Saharan Africa with high poverty rates, which has tripled its population in the last half century like many countries in the Sahel region. More specifically, it has increased from 4.5 to 18 million inhabitants. These demographic changes, combined with an intense migration and the import of new building materials, are modifying traditional ways of life. As a result, new housing typologies that are being built in the city outskirts differ greatly from traditional architecture. After several long-term stays and six months of fieldwork, the authors have explored different ways of life of the Mossi and Peul cultures. Results show that introduction of land ownership, real-estate speculation, and an increasing scarcity of natural resources are forcing these cultures to change their ways of life.